Kicking the Habit: Rethinking Academic Hypermobility in the Anthropocene - Crumley-Effinger, Max; Torres-Olave, Blanca (Journal of International Students, 2021)
Examining the hypermobility of many “elite” academic workers, this article situates mobility within the context of higher education and sustainability, decoloniality, and institutionalized expectations for academic travel. The mobility of HEI workers is described in relation to Anthropogenic climate change (ACC), which highlights the need for: (a) critical examination of and responses to the carbon footprint of academic workers; (b) exerting pressure to reduce greenhouse gas (GHG) production associated with expected mobility; and (c) deliberate changes to professional mobility approaches that take into account issues of equity vis-à-vis knowledge production, the effects of ACC, and GHG production from academic air travel. We offer an instrument—in the form of queries—to provide starting points for individual deliberations and collective actions to begin addressing these three issue areas.